Socio-economic inequalities in health care utilisation in Norway: a population based cross-sectional survey - Hansen Anne; Halvorsen Peder A; Ringberg Unni; Førde Olav (BMC, 2012)
Abstract Background Norway provides universal health care coverage to all residents, but socio-economic inequalities in health are among the largest in Europe. Evidence on inequalities in health care utilisation is sparse, and the aim of this population based study was to investigate socio-economic inequalities in the utilisation of health care services in Tromsø, Norway. Methods We used questionnaire data from the cross-sectional Tromsø Study, conducted in 2007-8. All together 12,982 persons aged 30-87 years participated with the response rate of 65.7%. This is slightly more than one third of the total population (33.8%) in the mentioned age group in Tromsø municipality. By logistic regression analyses we studied associations between household income, education and self-rated occupational status and the utilisation of general practitioner, somatic and psychiatric specialist outpatient services. The outcome variables were probability and frequency of use during the previous 12 months. Analyses were stratified by gender and adjusted for age, marital status, and self-rated health. Results Self-rated health was the dominant predictor of health care utilisation. Women's probability of visiting a general practitioner did not vary by socio-economic status, but high income was associated with less frequent use (odds ratio [OR] for trend 0.89, 95% confidence interval [CI] 0.81-0.98). In men, high income predicted lower probability and frequency of general practitioner utilisation (OR for trend 0.85, CI 0.76-0.94, and 0.86, 0.78-0.95, respectively). Women's probability of visiting a somatic specialist increased with higher income (OR for trend 1.11, CI 1.01-1.21) and higher education (OR for trend 1.27, CI 1.16-1.39). We found the same trends for men, though significant only for education (OR for trend 1.14, CI 1.05-1.25). The likelihood of visiting psychiatric specialist services increased with higher education and decreased with higher income in women (OR for trend 1.57, CI 1.24-1.98, and 0.69, 0.56-0.86, respectively), but did not vary significantly by socio-economic variables in men. Higher income predicted more frequent use of psychiatric specialist services in men (OR for trend 2.02, CI 1.12-3.63). Conclusions This study revealed important inequalities in the utilisation of health care services in Norway, inequalities which may contribute to sustaining inequalities in health outcomes.